PENGARUH CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK INDOCAFE PADA PT PRIMA BINTANG DISTRIBUSINDO - Iwan Iwan; Asron Saputra (Magister Manajemen STIE Bank BPD Jateng, 2020)
The purpose of this paper is to determine the effect of brand image and promotion on purchasingdecisions PT prima brima distribusindo. The research was done by spreading the quaterner, while theresearch method using Non-probability Sampling.The t test shows that the magnitude of t for Brand Image (X 1 ) is 2.062 and the value of t arithmetic for promotion (X 2 ) is 11,574. all of which show larger than t table is 1,978. so the hypothesis that states brand image and promotion have a positive effect partially on purchasing decision at PT prima bintang distribusindo, F test, F calculated > F table or 69.690 > 2.67 or signification level (sig) 0.000 < 0.05 so that the hypothesis that states brand image and promotion together affect the purchasing decision at PT prima bintang distribusindo and coefficient of determination shows that brand image and promotion influence 51,9% to purchasing decision at PT. prima bintang distribusindo.